Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan pada PT. Sukses Expamet - Endang Sugiarti (Mahesa Research Center, 2020)
This study aims to determine the effect of work environment and compensation on employee performance at PT. Expamet success. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the work environment has a significant effect on employee performance by 53.6%, hypothesis testing obtained t count> t table or (7,815> 2,006). Compensation has a significant effect on employee performance by 43.3%, hypothesis testing is obtained t count> t table or (6.358> 2.006). Work environment and compensation simultaneously have a significant effect on employee performance with the regression equation Y = 8.506 + 0.426X1 + 0.366X2 and the contribution of the effect is 62.4%, the hypothesis test is obtained F count> F table or (43.076> 2.780).